2021
DOI: 10.1186/s40001-021-00507-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgery-related muscle quantity and muscle quality loss and their impact on outcome

Abstract: Background Surgery-related loss of muscle quantity negatively affects postoperative outcomes. However, changes of muscle quality have not been fully investigated. A perioperative intervention targeting identified risk factors could improve postoperative outcome. This study investigated risk factors for surgery-related loss of muscle quantity and quality and outcomes after liver resection for colorectal liver metastasis (CRLM). Methods Data of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Similarly, surgery can also cause the loss of muscle mass and muscle strength, such as acute loss of skeletal muscle mass after major hepatectomy 22 ; the surgery‐related muscle loss is as high as 7.1% (±5.7%) after liver resection for colorectal liver metastases. 23 However, there is no relevant evidence regarding whether it can be recovered or how long it would take. Therefore, there is no suitable exclusion criterion for this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, surgery can also cause the loss of muscle mass and muscle strength, such as acute loss of skeletal muscle mass after major hepatectomy 22 ; the surgery‐related muscle loss is as high as 7.1% (±5.7%) after liver resection for colorectal liver metastases. 23 However, there is no relevant evidence regarding whether it can be recovered or how long it would take. Therefore, there is no suitable exclusion criterion for this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who undergo major abdominal surgery experience further loss in muscle mass, which can lead to worse post‐operative outcomes. 22 , 23 Some studies have shown that pre‐operative exercise, 24 nutritional intervention, 25 supplementation with leucine, 26 etc., can decrease sarcopenia, improving short‐term post‐operative outcomes in patients with sarcopenia. Therefore, if we can accurately detect or identify patients with sarcopenia at the first clinical encounter, it is expected that intervention measures could be applied before surgery to improve post‐operative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most surgeons recognized the importance of adequate perioperative nutritional status in optimizing patient outcomes. There was strong acknowledgement that malnutrition and the catabolic impact of the surgical stress response negatively impact postoperative recovery, as has been reported in observational studies of patients undergoing major GI surgery [3,4,31]. The surgeons also agreed that the preoperative phase provides an important window to ensure patients are fit to undergo surgery, with optimizing nutritional status being key to reducing risks associated with the surgical stress response.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, chronic liver disease or liver dysfunction would lead to altered protein turnover, malnutrition, deranged energy disposal, increased inflammation, and hormonal change, which in turn result in muscle depletion and occurrence of sarcopenia [ 41 , 42 ]. Therefore, development of muscle loss following liver resection seemed inevitable and had been documented [ 26 , 43 , 44 ]. In addition to studies assessing muscle wasting following conventional open liver surgery, Himura et al revealed that patients receiving laparoscopic liver resection would also experience muscle loss and deteriorated nutritional status, even in those without preoperative sarcopenia or severe postoperative complications [ 43 ].…”
Section: Discussionmentioning
confidence: 99%